Determination of an integrated set of principles, criteria, indicators and verifiers for the evaluation of ecological sustainability of forest management in Costa Rica - McGinley, Kathleen (2000)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica); 2000